2012
DOI: 10.1007/s10562-012-0773-9
|View full text |Cite
|
Sign up to set email alerts
|

One-pot Hydrothermal Synthesis of Mesoporous V-SBA-16 with a Function of the pH of the Initial Gel and its Improved Catalytic Performance for Benzene Hydroxylation

Abstract: V-SBA-16 catalysts with uniform cubic mesoporous structure were prepared by direct hydrothermal method as a function of the pH of the initial gel and characterized by ICP, XRD, TEM, N 2 adsorption-desorption, DRUV-vis and Raman spectra. The pH of the initial gel in synthesis of V-SBA-16 show important effects on the maintenance of well ordered mesoporous structure, introduced vanadium content and the incorporation of vanadium into the network of SBA-16 type mesoporous material. The initial gel system with a pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The maximum absorption band shows an obvious red shift to 405 nm, which can be associated with the presence of H x V 2 O 5 crystallites. Moreover, the absorption band of VG-N-A400 further shifts to higher wavelength and the maximum absorption signal begin from about 485 nm, which can be assigned to the formation of bulk V 2 O 5 species [23,47].…”
Section: Synthesis and Characterization Of Vo X /Rgo Compositesmentioning
confidence: 96%
“…The maximum absorption band shows an obvious red shift to 405 nm, which can be associated with the presence of H x V 2 O 5 crystallites. Moreover, the absorption band of VG-N-A400 further shifts to higher wavelength and the maximum absorption signal begin from about 485 nm, which can be assigned to the formation of bulk V 2 O 5 species [23,47].…”
Section: Synthesis and Characterization Of Vo X /Rgo Compositesmentioning
confidence: 96%
“…Similar decrease of surface area and pore volume for high V loading samples (above 3 wt%) was also observed by other authors for vanadium containing SBA-15 materials. 17,18 The average pore diameters of vanadosilicate SBA-3 synthesized at low pH (<1) of both series are higher than these of their silica counterparts synthesized at the same pH. The pore size for both series increases with the pH applied during synthesis up to value 2.2 and then declines along with further pH increase.…”
Section: Vo 2+ + H 2 O/ [Ho-v]o] + + H +mentioning
confidence: 95%
“…Their high performance has been attributed to the wide dispersion of highly reducible vanadium-isolated species with tetrahedral coordination. [17][18][19][20][21][22] On the other hand, it was shown that all silica mesoporous materials modied with vanadium are active catalyst in propene epoxidation with N 2 O as an oxidant. The best results were obtained with catalysts prepared by impregnation of silica SBA-3 with vanadium ions.…”
Section: Introductionmentioning
confidence: 99%
“…Various supported vanadium catalysts, such as V/SiO 2 [10], VxOy@C [11], V-AlPO 5 [12] VOx/SBA-15 [13], VOx/TiO 2 [14], V-SBA-16 [15] and VO 2 -defects/ MWCNT [16] have been developed. The dispersed vanadium species would be easily released from the supports in acetic acid aqueous solution that is the most commonly used solvent for this reaction [17], and as a result, the catalysts exhibited poor catalytic stability [18].…”
Section: Introductionmentioning
confidence: 99%